RADIOLOGICAL FEATURES OF LUNG ABSCESS - Vina Tri Septiana; Budi Yulhasfi Febrianto; Rahmi Afifi; Gurmeet Singh (Jurnal EduHealth, 2021)
Lung abscess is still a significant cause of morbidity and mortality. The worldwide mortality rate ranges from 15% to 20%. Radiologically, lung abscesses appear as single or multiple cavities that can mimic many other pulmonary pathological processes which pose a challenge for radiologists to understand this disease. Failure in early diagnosis and treatment can lead to a poor prognosis. Radiological examinations such as conventional radiography, computed tomography (CT) scan, ultrasonography (US and magnetic resonance imaging are available in establishing the diagnosis of lung abscess where CT scan has the best diagnostic performance. The use of appropriate radiological modalities is expected to help rule out many other differential diagnoses, so that an accurate diagnosis can be made.